Diversity in growth and protein degradation by dairy relevant lactic acid bacteria species in reconstituted whey - Pescuma, Micaela (2012)
The high nutritional value of whey makes it an interesting substrate for the development of fermented foods. The aim of this work was to evaluate the growth and proteolytic activity of sixty-four strains of lactic acid bacteria in whey to further formulate a starter culture for the development of fermented whey-based beverages. Fermentations were performed at 37°C for 24 h in 10 and 16% (w/v) reconstituted whey powder. Cultivable populations, pH, and proteolytic activity (o-phthaldialdehyde test) were determined at 6 and 24 h incubation. Hydrolysis of whey proteins was analysed by Tricine SDS-PAGE. A principal component analysis (PCA) was applied to evaluate the behaviour of strains. Forty-six percent of the strains grew between 1 and 2 Δlog CFU/ml while 19% grew less than 0·9 Δlog CFU/ml in both reconstituted whey solutions. Regarding the proteolytic activity, most of the lactobacilli released amino acids and small peptides during the first 6 h incubation while streptococci consumed the amino acids initially present in whey to sustain growth. Whey proteins were degraded by the studied strains although to different extents. Special attention was paid to the main allergenic whey protein, β-lactoglobulin, which was degraded the most by Lactobacillus acidophilus CRL 636 and Lb. delbrueckii subsp. bulgaricus CRL 656. The strain variability observed and the PCA applied in this study allowed selecting appropriate strains able to improve the nutritional characteristics (through amino group release and protein degradation) and storage (decrease in pH) of whey.